2016
DOI: 10.1016/j.ymeth.2016.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Chemical synthesis of RNA with site-specific methylphosphonate modifications

Abstract: Methylphosphonate(mP)-modified RNA serves as valuable probe to evaluate biomolecular interactions between the nucleic acid backbone and binding partners, such as proteins or small molecules. Here, we describe an efficient workflow for the synthesis of RNA with a single mP modification in diastereomerically pure form. While the automated assembly of mP-modified RNA is straightforward, its deprotection under basic conditions is challenging; a carefully optimized step-by-step procedure is provided. In addition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Both separations closely followed previous reports. 38,39 As previously observed, the Rp-PSO isomer eluted first. 39 Ultraviolet (UV) Thermal Melting Experiments with PO2-, PSO-, and PS2-SRL RNAs.…”
Section: ■ Experimental Proceduressupporting
confidence: 83%
See 1 more Smart Citation
“…Both separations closely followed previous reports. 38,39 As previously observed, the Rp-PSO isomer eluted first. 39 Ultraviolet (UV) Thermal Melting Experiments with PO2-, PSO-, and PS2-SRL RNAs.…”
Section: ■ Experimental Proceduressupporting
confidence: 83%
“…The dAMePO-SRL was synthesized according to previously published protocols. 38 After completion of the automated synthesis, oligonucleotides were manually released from support and deprotected using 30% NH 4 OH and 5% diethylamine for 6 h at 55 °C. After filtration through a nylon syringe filter (0.45 μm), 2′hydroxyl groups were deprotected by treatment with Et 3 N• 3HF at 60 °C for 10 min.…”
Section: ■ Experimental Proceduresmentioning
confidence: 99%
“…Among these, the methylphosphonates (MPO) are the most important ( Figure 10 ). Their synthesis is simple by using methylphosphonoamidites in conventional oligonucleotide synthesis [ 128 , 129 ]. The MPOs are very resistant against nucleases.…”
Section: Artificial Nucleic Acidsmentioning
confidence: 99%
“…Abeydeera et al [ 94 ] modified the single nucleotide of aptamer with phosphorodithioate, and the X-ray co-crystal structure of the α-thrombin: aptamer complex revealed a locally induced fitting rearrangement of this nucleotide, which significantly enhanced the affinity of aptamer by 1000-fold. However, some studies have shown that if the modified site and configuration of the modification are not appropriate, the formation of double strands with complementary DNA/RNA may be affected [ 95 ].…”
Section: Post-selex Optimization Of Aptamersmentioning
confidence: 99%